Sustained life-like waveform capnography after human cadaveric tracheal intubation. Issue 3 (8th October 2013) - Reid, Cliff; Lewis, Anthony; Habig, Karel; Burns, Brian; Billson, Frank; Kunkel, Sven; Fisk, Wesley
Abstract : Introduction: Fresh frozen cadavers are effective training models for airway management. We hypothesised that residual carbon dioxide (CO2 ) in cadaveric lung would be detectable using standard clinical monitoring systems, facilitating detection of tracheal tube placement and further enhancing the fidelity of clinical simulation using a cadaveric model. Methods: The tracheas of two fresh frozen unembalmed cadavers were intubated via direct laryngoscopy. Each tracheal tube was connected to a self-inflating bag and a sidestream CO2 detector. The capnograph display was observed and recorded in high-definition video. The cadavers were hand-ventilated with room air until the capnometer reached zero or the waveform approached baseline. Results: A clear capnographic waveform was produced in both cadavers on the first postintubation expiration, simulating the appearances found in the clinical setting. In cadaver one, a consistent capnographic waveform was produced lasting over 100 s. Maximal end-tidal CO2 was 8.5 kPa (65 mm Hg). In cadaver two, a consistent capnographic waveform was produced lasting over 50 s. Maximal end-tidal CO2 was 5.9 kPa (45 mm Hg). Conclusions: We believe this to be the first work to describe and quantify detectable end-tidal capnography in human cadavers. We have demonstrated that tracheal intubation of fresh frozen cadavers can be confirmed by life-like waveform capnography. This requires further validation in a larger sample size.